ANALISIS PEMBUATAN KATALOG NAIL ART BERBASIS AUGMENTED REALITY PADA FEFE HAIR & BEAUTY SALON - Zhella Ley Kharismatara; Agus Fatkhurohman (Universitas Amikom Yogyakarta, 2021)
In this case, nail art is the most popular treatment for customers, but according to the owner of Fefe Hair & Beauty Salon, customers do not have more knowledge of nail art in terms of type, color, and treatment method. Therefore, it is necessary to develop technology that is able to explain this for customers at Fefe Hair & Beauty Salon so that customers do not only guess about what is being explained, but customers will also get education directly from the technology made. To solve this problem, the research will be carried out in several stages. The research method used in this research is interviews, literature and questionnaires. Then, the method for making applications is to use the Multimedia Development Life Cycle (MDLC). In the application used, this study uses Adobe Illustrator, Adobe XD, NotePad ++ and Unity.